Hydrothermally Synthesized SnS2 Anode Materials with Selectively Tuned Crystallinity - Akzhan Bekzhanov; Nurgul Daniyeva; Qixiang Jiang; Yuri Surace; Freddy Kleitz; Damian Cupid (Small Science)
SnS2‐based anode active materials for lithium‐ion battery applications are synthesized with varying degrees of crystallinity via a hydrothermal method, and their electrochemical performance properties are assessed. Different ratios of tin chloride and thioacetamide precursors are used and studied to control the crystallization. In situ electrochemical impedance spectroscopy and galvanostatic intermittent titration technique experiments are used to study the lithium‐ion diffusion kinetics into the crystal structures and the conversion reaction mechanisms for discharge up to x ≈ 2.08 moles of lithiation per SnS2, equivalent to a discharge capacity of 300 mAh g−1. Transmission electron microscopy reveals the presence of amorphous and crystalline domains, as well as the existence of additional Sn2S3 layers on one of the samples. The highest specific reversible capacity during cycling and rate performance are 598 mAh g−1 after 100 cycles and 605 mAh g−1 after rate capability test, which are obtained for the samples prepared with the 1:4 tin chloride to thioacetamide ratio.